2015
DOI: 10.5755/j01.eee.21.6.13763
|View full text |Cite
|
Sign up to set email alerts
|

BoostEMD: An Extension of EMD Method and Its Application for Denoising of EMG Signals

Abstract: The paper presents a novel extension of the Huang's Empirical Mode Decomposition (EMD) method, called BoostEMD, that allows calculating higher order Intrinsic Mode Functions (IMFs) that capture higher frequency empirical mode oscillations (empiquencies) in the EMG (electromyography) data. We describe the use of the second order IMFs for denoising physical action EMG signals.We demonstrate the efficiency of denoising by performing classification of EMG data before and after application of the denoising procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Since the EPOC headset is not intended for finer signal detection, the electrodes pick up a lot of noise. Several techniques can be used to increase the Signal-to-Noise Ratio (SNR) such as band-pass filtering, averaging or class adaptive denoising [ 74 ], DCT compression [ 75 ], signal decomposition and thresholding [ 76 ], or nonlinear signal operators [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since the EPOC headset is not intended for finer signal detection, the electrodes pick up a lot of noise. Several techniques can be used to increase the Signal-to-Noise Ratio (SNR) such as band-pass filtering, averaging or class adaptive denoising [ 74 ], DCT compression [ 75 ], signal decomposition and thresholding [ 76 ], or nonlinear signal operators [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…A further extension of the EMD method called BoostEMD was design by [105].This variant of the EMD method allows for use of higher orders IMFs. The authors conducted a comparative study with the classic EMD for classification accuracy and found their method was more effective.…”
Section: Denoising After Empirical Mode Decomposition (Emd)mentioning
confidence: 99%
“…However, these signal processing methods are not suitable for analyzing the nonstationary underwater acoustic signals, the feature extraction results cannot reflect the real features for the target signal well [ 8 , 9 ]. As the rapid development of signal processing technology, some signal processing methods for nonlinear and nonstationary signals are proposed, such as empirical mode decomposition (EMD) [ 10 , 11 ], local mean decomposition (LMD) [ 12 , 13 ], variational mode decomposition (VMD) [ 14 , 15 ], and their improved algorithms [ 16 , 17 , 18 , 19 ]. Some of these mode decomposition algorithms have been applied to feature extraction of underwater acoustic target signals, which can be divided into three groups based on the extracted feature information: energy feature extraction, complexity feature extraction, and frequency feature extraction.…”
Section: Introductionmentioning
confidence: 99%